Impacts of land use changes on net ecosystem production in the Taihu Lake Basin of China from 1985 to 2010. Issue 3 (25th March 2017) - Xu, Xibao; Yang, Guishan; Tan, Yan; Tang, Xuguang; Jiang, Hong; Sun, Xiaoxiang; Zhuang, Qianlai; Li, Hengpeng
Abstract: Land use changes play a major role in determining sources and sinks of carbon at regional and global scales. This study employs a modified Global biome model‐biogeochemical cycle model to examine the changes in the spatiotemporal pattern of net ecosystem production (NEP) in the Taihu Lake Basin of China during 1985–2010 and the extent to which land use change impacted NEP. The model is calibrated with observed NEP at three flux sites for three dominant land use types in the basin including cropland, evergreen needleleaf forest, and mixed forest. Two simulations are conducted to distinguish the net effects of land use change and increasing atmospheric concentrations of CO2 and nitrogen deposition on NEP. The study estimates that NEP in the basin decreased by 9.8% (1.57 Tg C) from 1985 to 2010, showing an overall downward trend. The NEP distribution exhibits an apparent spatial heterogeneity at the municipal level. Land use changes during 1985–2010 reduced the regional NEP (3.21 Tg C in year 2010) by 19.9% compared to its 1985 level, while the increasing atmospheric CO2 concentrations and nitrogen deposition compensated for a half of the total carbon loss. Critical measures for regulating rapid urban expansion and population growth and reinforcing environment protection programs are recommended to increase the regional carbon sink. Key Points: The effects of land use changes and other environmental changes on NEP were separated using a modified BIOME‐BGC model Land use changes during 1985–2010 reduced NEP by more than 20% Increasing CO2 concentration and nitrogen deposition compensated for a half of the total carbon loss